2010
DOI: 10.1302/0301-620x.92b2.22688
|View full text |Cite
|
Sign up to set email alerts
|

A case of necrotising fasciitis caused by Pseudomonas aeruginosa

Abstract: Necrotising fasciitis is a rare but severe infection of soft-tissue associated with rapid progression, systemic toxicity and high mortality. Monomicrobial necrotising fasciitis caused by Pseudomonas aeruginosa is exceptionally uncommon with only 12 cases reported in the literature. We describe a fatal case with an atypical presentation in a patient following spinal decompression for a metastasis from prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Pseudomonas aeruginosa infections of healthy skin are uncommon (14). Pseudomonas aeruginosa may cause localized epidermal infections (the green nail syndrome and webbed space infections), moderately serious infections (cutaneous folliculitis and otitis externa), and soft-tissue infections with peri-vasculitis secondary due to bacteremia (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Pseudomonas aeruginosa is reported common causes of nosocomial infections, and exhibits resistance to a wide range of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas aeruginosa infections of healthy skin are uncommon (14). Pseudomonas aeruginosa may cause localized epidermal infections (the green nail syndrome and webbed space infections), moderately serious infections (cutaneous folliculitis and otitis externa), and soft-tissue infections with peri-vasculitis secondary due to bacteremia (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Pseudomonas aeruginosa is reported common causes of nosocomial infections, and exhibits resistance to a wide range of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…necrotizing fasciitis caused by Pseudomonas aeruginosa is exceptionally uncommon, and only few cases have been reported in the literature search (9)(10)(11)(12)(13)(14)(15)(16). Our previous study has reported three cases of monomicrobial necrotizing fasciitis caused by Pseudomonas aeruginosa, and one of them died (5) The enrolled patients were categorized into two groups: the death group and the survival group.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Immunocompromised patients also have a 2-fold higher rate of necrotizing soft-tissue infection-related mortality [ 9 ]. Monomicrobial necrotizing fasciitis caused by P. aeruginosa is very rare with only a few cases reported in the literature [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monomicrobial pseudomonal necrotising fasciitis, however, is very rare,2 5 6 but it has been described in patients with underlying malignancy,5 including children with acute lymphoblastic leukaemia,7 and in immunocompromised patients 1 5…”
Section: Discussionmentioning
confidence: 99%
“…Necrotising fasciitis is a severe soft tissue infection with a high morbidity and mortality 1 2. Good outcome depends on early diagnosis and aggressive surgical excision of necrotic tissue 1.…”
Section: Introductionmentioning
confidence: 99%